Black Sunday [videorecording (Blu-Ray)] - Frankenheimer, John, 1930-2002; Shaw, Robert, 1927-1978; Dern, Bruce; Keller, Marthe; Harris, Thomas, 1940- (Arrow Video, 2023)
A Black September terrorist group attempts to blow up a Goodyear blimp hovering over the Super Bowl stadium with 80,000 people, including the U.S. president, in attendance.